آليات وسبل ترقية الاستثمار السياحي في ولاية بسكرة كمنطقة جذب سياحي - بركان, دليلة (جامعة الوادي - University of Eloued, 2019)
تهدف هذه المداخلة إلى دراسة سبل وآليات ترقية الاستثمار السياحي في الجزائر عامة وولاية بسكرة خاصة، باعتبار ما تمتلكه من مقومات سياحية طبيعية، حضارية، ثقافية، دينية ،...؛ ففي الوقت الراهن أضحت ترقية الاستثمار السياحي محور اهتمام الحكومة، لذلك فهي تسعى جاهدة لاستغلال المقومات السياحية بشكل عقلاني، من خلال وضع الآليات المناسبة التي تهدف إلى جذب المستثمرين المحليين والأجانب، ومساعدتهم على تجاوز المعوقات والمشاكل التي قد تواجههم كمشكل التمويل، العوائق الإدارية، القانونية والبيروقراطية...، وذلك من خلال سن جملة من التشريعات والقوانين المنظمة واتخاذ التدابير اللازمة، من أجل تحفيز المستثمرين على الاستثمار في القطاع السياحي، الذي يعد عنصرا حيويا وفعالا في تحقيق التنمية السياحية. The aim of this intervention is to study the ways and mechanisms to upgrade tourist investment in Algeria in general and in Biskra in particular, considering that it possesses the elements of a natural tourist ,civilization, cultural, religious;... ,At present , promotion of tourism investment has become the focus of the Government's attention Therefore, it strives to exploit the tourism components rationally , through the development of appropriate mechanisms aimed at attracting local and foreign investors , and help them overcome the obstacles and problems that may face them such as funding, administrative obstacles, legal and bureaucratic ..., through the enactment of a number of legislation, laws and measures to encourage investors to invest in the tourism sector, a vital and effective element in achieving tourism development.
Mechanisms and ways to upgrade tourism investment in the state of Biskra as a tourist attraction
مقال
Keywords: tourism investment, obstacles to tourism investment, mechanisms to upgrade tourist investment ,BISKRA